University faculty attitudes and knowledge about learning disabilities. Issue 5 (28th July 2020) - Lipka, Orly; Khouri, Marlyn; Shecter-Lerner, Michal
ABSTRACT: Adults with learning disabilities (LD) constitute one of the fastest growing populations of students attending institutions of higher education. Faculty members play an important role in the adjustment and success of these students. The current study investigated the perceptions towards LD of faculty members at a public university in Israel. Specifically, the study examined the level of contact, attitudes, knowledge, and training of faculty members with respect to students with LD. The results demonstrated that faculty members overall had a significant amount of contact with and held positive attitudes towards students with LD. However, it appeared that faculty members would benefit from information regarding the current definition of LD, related legislation about LD and other disabilities, and training and support services for LD. Implications for practice and further research are discussed.